Rights and Future Persons: The Promise of Arguments from Present People’s Identity - Könczöl, Miklós (Public Governance, Administration and Finances Law Review, 2023)
This paper examines the ways the two fundamental problems regarding the rights of future persons/generations (the non-existence problem and the non-identity problem) are usually tackled in scholarship. It is argued that while rights cannot be properly attributed to future people, rights in respect to future generations can be based on present persons’ identity.